Application Progress of Rehabilitation Exoskeleton Robot in Limb Rehabilitation - Kaifang Wang; Hui Cao; Mengmeng Xing; Feng Yang; Junzhong Zhang; Jin'gang Ma (Jixie chuandong)
Rehabilitation exoskeleton robots are mainly applied to patients with dysfunctional limb movements，and patients can complete rehabilitation treatment through phased，scientific and precise training of the exoskeleton. However，there are many types and forms of rehabilitation exoskeleton robots on the market at present，and how to categorize them will become a difficult problem. The domestic and international research progress of rehabilitation exoskeleton robots in recent years is summarized. The current representative rehabilitation exoskeleton robots are classified according to their different assisted positions in the human body； A detailed overview of different driving methods of rehabilitation exoskeleton robots is given and the current research status of different driving methods are analyzed； The targeted training mode of the rehabilitation exoskeleton robot is analyzed from the perspective of adopting the corresponding training mode according to the stage of rehabilitation treatment. The technical difficulties in current exoskeleton rehabilitation treatment is summarized and provides an outlook， aiming to provide a reference for future research on rehabilitation exoskeleton robots.